2008
DOI: 10.1097/mao.0b013e318182025a
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Meniett Device in Patients With Ménière's Disease

Abstract: The Meniett device is a minimally invasive, nondestructive treatment that may be used to provide longer-term reduction of vestibular symptoms in patients with Ménière's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…A long-term follow-up showed 75% improvement in frequency and severity of spells,36 which is similar to the improvement in untreated patients. This is a relatively expensive device, and a cost–benefit analysis is lacking.…”
Section: Devicessupporting
confidence: 65%
“…A long-term follow-up showed 75% improvement in frequency and severity of spells,36 which is similar to the improvement in untreated patients. This is a relatively expensive device, and a cost–benefit analysis is lacking.…”
Section: Devicessupporting
confidence: 65%
“…Nine studies reported PTA before and after Meniett treatment, eight studies reported frequency of vertigo before and after treatment, and seven studies reported the AAO‐HNS functional score before and after treatment . Egger tests for all three study sets showed that there was no significant publication biases among these studies for PTA (P = 0.33), AAO‐HNS function score ( P = 0.48), and frequency of vertigo ( P = 0.07).…”
Section: Resultsmentioning
confidence: 95%
“…Figure shows the flow chart of the search results. Of 113 studies identified, 18 studies met criteria for a thorough review . Table and Table provide the characteristics of the 18 studies (type of study, number of patients, PTA before and after Meniett treatment, vertigo scores before and after treatment).…”
Section: Resultsmentioning
confidence: 99%
“…Labyrinthectomy results in the unequivocal, total elimination of hearing in all cases. It is not surprising that less destructive procedures for alleviating vertigo without causing hearing deficits or other worrisome complications have been the source of considerable interest and scrutiny, including the Meniett device,24, 25 transtympanic gentamicin perfusion,26–28 and intratympanic steroid injection 29. In particular, EMSS appears to have regained popularity recently due to its low‐risk safety profile, effectiveness in controlling episodes of vertigo, and in some cases improvement in hearing 1.…”
Section: Discussionmentioning
confidence: 99%